Vitamin D and multiple sclerosis: epidemiology, immunology, and genetics - Simon, Kelly Claire (Curr Opin Neurol, 2012)
PURPOSE OF REVIEW: To provide a brief update of new research findings on the role of vitamin D in multiple sclerosis (MS). RECENT FINDINGS: Evidence continues to accumulate supporting a protective role for vitamin D in MS etiology and progression. Notable recent findings are that high 25-hydroxyvitamin D (25(OH)D) at the time of a first demyelinating event predicts a lower MS risk , and a decreased risk of MS among offspring whose mothers had high predicted 25(OH)D levels. While a small vitamin D intervention study did not find an association between vitamin D and MS progression, this study had little statistical power, and larger trials will be needed to assess the therapeutic potential of vitamin D. Recent immunological studies also show modulation of the immune system by vitamin D that may be favorable for preventing or slowing the progression of MS. The demonstration that rare variants in CYP27B1, which encodes the enzyme that converts vitamin D to its active form, are strongly associated with MS risk supports a causal role of vitamin D deficiency as a risk factor for MS. SUMMARY: Research on the nature of the association between vitamin D and MS etiology and progression continues to progress, however, additional research on the timing and dose-response relationship will be crucial for designing future prevention and treatment trials.